The Usborne animated children's encyclopedia : book and CD-ROM - Elliott, Jane.; Craig, Annabel; Crawford, Susan; King, Colin; Wilkes, Angela; Usborne Publishing Ltd. ([London : Usborne ; Tulsa, Okla. : EDC Publishing, 1999)
Illustrations and text teach children about a variety of topics related to space, natural life, history, and people; includes a CD-ROM with animations, sounds, music, and games designed to reinforce the lessons in the encyclopedia.
Includes index.
5.3
3-6.
3-6
System requirements for CD-ROM: 486DX/33MHz; 8MB RAM; 10MB free hard-disk space; WIN 3.1/WIN 95/WIN 98; 256-color display; 2x CD-ROM drive; sound card; speakers; mouse.
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; Encyclopedias and dictionaries